At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To find [tex]\( P(3) \)[/tex] for the polynomial [tex]\( P(t) = t^4 - t^3 + 3t^2 - 5 \)[/tex], follow these steps:
1. Substitute [tex]\( t = 3 \)[/tex] into the polynomial.
2. Compute each term separately.
Let's start by substituting [tex]\( t = 3 \)[/tex] into each term of the polynomial:
[tex]\[ P(t) = t^4 - t^3 + 3t^2 - 5 \][/tex]
Substituting [tex]\( t = 3 \)[/tex]:
[tex]\[ P(3) = 3^4 - 3^3 + 3 \cdot 3^2 - 5 \][/tex]
Now, calculate each term:
- First term: [tex]\( 3^4 \)[/tex]
[tex]\[ 3^4 = 3 \times 3 \times 3 \times 3 = 81 \][/tex]
- Second term: [tex]\( -3^3 \)[/tex]
[tex]\[ 3^3 = 3 \times 3 \times 3 = 27 \][/tex]
Therefore,
[tex]\[ -3^3 = -27 \][/tex]
- Third term: [tex]\( 3 \cdot 3^2 \)[/tex]
[tex]\[ 3^2 = 3 \times 3 = 9 \][/tex]
Therefore,
[tex]\[ 3 \cdot 9 = 27 \][/tex]
- Fourth term: [tex]\( -5 \)[/tex]
This term is already simplified as [tex]\( -5 \)[/tex].
Now, combine all the calculated terms together:
[tex]\[ P(3) = 81 - 27 + 27 - 5 \][/tex]
Perform the arithmetic operations step-by-step:
[tex]\[ 81 - 27 = 54 \][/tex]
[tex]\[ 54 + 27 = 81 \][/tex]
[tex]\[ 81 - 5 = 76 \][/tex]
Thus,
[tex]\[ P(3) = 76 \][/tex]
Therefore, [tex]\( P(3) \)[/tex] is [tex]\( \boxed{76} \)[/tex].
1. Substitute [tex]\( t = 3 \)[/tex] into the polynomial.
2. Compute each term separately.
Let's start by substituting [tex]\( t = 3 \)[/tex] into each term of the polynomial:
[tex]\[ P(t) = t^4 - t^3 + 3t^2 - 5 \][/tex]
Substituting [tex]\( t = 3 \)[/tex]:
[tex]\[ P(3) = 3^4 - 3^3 + 3 \cdot 3^2 - 5 \][/tex]
Now, calculate each term:
- First term: [tex]\( 3^4 \)[/tex]
[tex]\[ 3^4 = 3 \times 3 \times 3 \times 3 = 81 \][/tex]
- Second term: [tex]\( -3^3 \)[/tex]
[tex]\[ 3^3 = 3 \times 3 \times 3 = 27 \][/tex]
Therefore,
[tex]\[ -3^3 = -27 \][/tex]
- Third term: [tex]\( 3 \cdot 3^2 \)[/tex]
[tex]\[ 3^2 = 3 \times 3 = 9 \][/tex]
Therefore,
[tex]\[ 3 \cdot 9 = 27 \][/tex]
- Fourth term: [tex]\( -5 \)[/tex]
This term is already simplified as [tex]\( -5 \)[/tex].
Now, combine all the calculated terms together:
[tex]\[ P(3) = 81 - 27 + 27 - 5 \][/tex]
Perform the arithmetic operations step-by-step:
[tex]\[ 81 - 27 = 54 \][/tex]
[tex]\[ 54 + 27 = 81 \][/tex]
[tex]\[ 81 - 5 = 76 \][/tex]
Thus,
[tex]\[ P(3) = 76 \][/tex]
Therefore, [tex]\( P(3) \)[/tex] is [tex]\( \boxed{76} \)[/tex].
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.